Phase and thermal stability in Ti3SiC2 and Ti3SiC2/TiC/TiSi2 systems - Pang, Wei Kong; Oo, Zeya; Peterson, V; Low, It Meng (Woodhead Publishing Limited, 2012)
It is known that Ti3SiC2 is the only stable ternary compound in the Ti-Si-C system; however the preparation of pure Ti3SiC2 is very difficult as there are always impurities. The properties of these Ti3SiC2 composites can be enhanced or weakened by these impurities. In this chapter, the effect of argon and high vacuum annealing on the phase stability and phase transitions of highly-pure Ti3SiC2 and Ti3SiC2/TiCx/TiSi2 composites up to 1550 dgreesC has been studied using in situ neutron diffraction. The role of TiCx and/or TiSi2 in the thermal stability of Ti3SiC2 during argon or vacuum annealing has been discussed. The mechanism of Ti3SiC2 decomposition in vacuum has also been proposed. The decomposition rate of Ti3SiC2 was both dependent on temperature and dwell time, and exhibited a linear relationship with the dwell time and increased with temperature. Furhtermore, the activation energy for the formation and decomposition of Ti3SiC2 was determined using the Arrhenius equation. The kinetics of isothermal phase decomposition at 1500 degreesC was modelled using a modified Avrami equation.